Does the Cancellation Victory Foreign Nationals in Local Democracy: Evidence from United Kingdom - Siboy, Ahmad; Bastomi, Ahmad (Journal of Human Rights, Culture and Legal System, 2024)
The main requirement to become a regional head candidate is to be an Indonesian citizen. In the 2020 Pilkada, it was found that a foreign citizen won the Regional Head Election. This certainly raises a legal dilemma or polemic regarding the inauguration process. Whether the person concerned can be inaugurated as regional head or canceled. The formulation of the problem raised in this research is about the legal implications of the victory of foreigners in the Regional Head Election and the legal construction of the cancellation of the inauguration. This research is normative juridical research with a concept approach, legislation approach, and case approach. The results of the study found four things that resulted from the victory of foreigners in the Regional Head Election. Namely, the weakness of the regulation, the negligence of the organizers, the validity period of the dispute resolution of the limited nomination requirements, and the confusion to advance or continue at the inauguration stage. The choice of legal construction as a solution that can be taken is to cancel the inauguration of foreign election winners. The cancelation process can go through the judicial process through the mechanism of disputing the results in the Constitutional Court. Cancellation of the inauguration can also be done by the executive body through a decision from the Ministry of Home Affairs.